A Comparative Study of Women’s Perceptions towards Wife Beating in Bangladesh: Based on Two Cross-Sectional Studies Research - Soni, Most Sifat Muntaha; Akter, Salma; Ireen, Shahjadi; Sultana, Rebeka; Begum, Mansura; Parvin, Shahanaj (Jagannath University Journal of Science, 2024)
The key indicator of declining domestic abuse is the opinion of women toward wife beating. The goal of this study was to compare women's attitudes toward being beaten by their husbands based on data from the Bangladesh Demographic and Health Survey (BDHS) conducted in 2014 and 2017–18. The outcome variable was the opinion of women on wife beating. Covariates included in the study were based on literature reviews. A chi-square test was conducted to assess the association between outcome variables and selected covariates. Concurrently, two distinct multivariate binary logistic regression models (for 2014 and 2017– 18, respectively) were employed to identify the variables connected to having this opinion of women. The most significant factors affecting women's views towards wife beating were women's education, age at marriage, place of residence, southern region, religion, employment status, and partner's educational background. This study also revealed that these factors remained significant in both years, despite the fact that the OR (odds ratio) varied widely. The odds of justifying wife beating among higher-educated women were 0. 78 times lower than those of uneducated women in 2014, which was o.67 times lower in 2017–18. Urban women were 18% less likely from 2014 to 2018 to agree with wife beating. Interestingly, Eastern Bengal was statistically significant in 2014, it was not in 2017-2018. The likelihood of accepting wife beating among Muslim women rose from 35% to 69% during the given period. In 2014, the wealth index was significantly associated with women's attitudes toward wife beating and showed that middle-class and rich women were 16% and 23% less likely to support wife beating, respectively, than poor women. However, this variable was not significant in 2017–18. Employed women are less likely to support wife beating than unemployed women in both years. Early married women are more likely to accept wife beatings than those of elderly married women (OR 1.22 in 2014 and OR 1.16 in 2017–18, respectively). The odds of justifying wife beating among women with a higher-educated partner decreased by 14% between 2014 and 2017–2018. Furthermore, social awareness campaigns should continue to alter women's attitudes regarding wife beating and should be updated in light of the significant factors identified in this study. Jagannath University Journal of Science, Volume 10, Number I, Jun 2023, pp. 19−26